Edukasi Upaya Pencegahan Gangguan Postur sejak Dini pada Anak di SDN 75 Bentang - Aling, Putri Maria Angelina; Ismail, Nur Syamsu; Haris, Nurul Fadhilah; Nur Madina, Salma; Nurafifah, Sitti (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Background: Postural abnormalities do not only occur in an elderly person but can also occur in children, namely elementary school age. Changes in posture that occur in children are related to wrong/bad sitting habits, non-ergonomic ways of standing, the habit of lifting weights in the wrong way, and the result of using the wrong backpack/exceeding body capacity so as to interfere with spinal growth and cause back pain to musculoskeletal disorders in children. Objective: This activity aims to provide education and counseling on good and correct posture to children at SDN 75 Bentang, Bentang Village, South Galesong District, Takalar Regency. Method: Education is carried out by providing material through presentations using power points and direct demonstrations. Results: Out of 30 students, after posture education, they were able to answer the questions given where there were no more students who met the "Less" category, the "Enough" category increased to 7 students (23%), and as many as 23 students (77%) met the "Good" category, so that the average student knowledge related to good and correct posture has increased. Conclusion: With education and efforts to prevent posture disorders from an early age, students and schools understand the importance of maintaining good and correct posture to avoid the risk of musculoskeletal disorders and posture defects.